Freqüência de pterígio no ambulatório de oftalmologia do Hospital Universitário Bettina Ferro de Souza - SANTOS NETO, Alberto Aguiar (2023)
The term pterygium becomes from a triangular or trapezoid fibrous and vascular proliferation, that grows to eye cornea and more frequent at the nasal incidence. The objective of this study is to show the incidence of this disease, it’s principal characteristics as gender, age, grade, anatomic eye installation, the patients complaints and your professions and their relations with the sun’s exposure at persons who live at the municipality of Belém, state of Pará. It’s a transversal, retrospective and descriptive study of 524 dossier of the patients of the Ambulatory of Ophthalmology of the Bettina Ferro de Sousa Hospital in Belém, state of Pará, on the period of August 2006 to July 2007.The results were submitted to statistical analysis with the calculation of the Qui-Square significance analysis with 95% and p equal to 0,05, than submitted to EPI-INFO Program, version 6,04. We concluded that didn’t exist any preference to gender, harmed eye, and no relation with people’s profession and place of work; it was most found over the age of 40 years and at the nasal incidence; the main patients questions were the loss of the vision.